1999
DOI: 10.1097/00007435-199902000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Herpes in the Time of AIDS: A Comparison of the Epidemiology of HIV-1 and HSV-2 in Young Men in Northern Thailand

Abstract: Although the seroprevalence levels of HSV-2 and HIV-1 were quite different in this cohort of Thai army conscripts in 1991, the patterns of infection in terms of demographic, residential, and behavioral variables were similar. Seroprevalence studies of HSV-2 in other populations, particularly where the HIV-1 epidemic is just beginning, may be useful in predicting which subgroups might be most vulnerable to the epidemic and could therefore benefit the most from public health intervention. Where differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…1 57 More recent studies have added further evidence supporting the association between HSV-2 antibodies and HIV. Significant correlations between HIV and HSV-2 specific antibodies were found in Zimbabwe among male factory workers (odds ratio (OR) 8.0), 58 in Tanzanian STI clinic attenders (OR 2.5), 59 in Thai military recruits with a history of ulcers in the past 3 years (prevalence ratio (PR) 14.4) and in those without a history of ulcers (PR 2.6), 60 and in STI patients in Lesotho (PR 1.9). 48 In the population based study in Masaka, Uganda, the initial phase showed high levels of HSV seropositivity-57% in men and 74% in women but an OR for association with HIV infection of only 1.2.…”
Section: Hsv As a Risk Factor For Hivmentioning
confidence: 99%
“…1 57 More recent studies have added further evidence supporting the association between HSV-2 antibodies and HIV. Significant correlations between HIV and HSV-2 specific antibodies were found in Zimbabwe among male factory workers (odds ratio (OR) 8.0), 58 in Tanzanian STI clinic attenders (OR 2.5), 59 in Thai military recruits with a history of ulcers in the past 3 years (prevalence ratio (PR) 14.4) and in those without a history of ulcers (PR 2.6), 60 and in STI patients in Lesotho (PR 1.9). 48 In the population based study in Masaka, Uganda, the initial phase showed high levels of HSV seropositivity-57% in men and 74% in women but an OR for association with HIV infection of only 1.2.…”
Section: Hsv As a Risk Factor For Hivmentioning
confidence: 99%
“…Periodic reactivation results in reinfection of the genital epithelium innervated by the infected dorsal root ganglia (DRG). Prophylactic immunization ideally would reduce infection of the genital epithelium and prevent latent infection of the ganglia, thereby eliminating the recurrent HSV-2 infections that provide opportunities for transmission to sex partners and newborns (60), as well as provide portals of entry for other pathogens such as human immunodeficiency virus (6,11,49). An understanding of how the response to immunization protects mucosally and systemically against subsequent HSV-2 genital infection would further the development of vaccines against sexually transmitted diseases, and HSV in particular.…”
mentioning
confidence: 99%
“…Seven studies were identified for Thailand and the seroprevalence for HSV-1 and HSV-2 was between 56.5% [113] to 91.0% [112] and 14.9% [110,111] to 80.0% [52], respectively. HSV-1 rates tended to be higher than HSV-2 rates, e.g., a study population of male army conscripts showed an HSV-1 seroprevalence of 77.0% and a lower HSV-2 seroprevalence of 14.9% [110,111]. The highest HSV-1 rate (91.0%) was reported among female sex workers, who had a lower HSV-2 rate (75.6%) [112].…”
Section: Herpes Simplex Virusmentioning
confidence: 99%